Leaf analysis of five native forest species - Villegas, Vicente Luiz Abarca; Cunha, Rubens José Pietsch; Politano, Walter; Garrido, Marco Antonio; Stipp, Nilsa A. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1976)
Analysis have been realized to evalue the content of macronutrients (N, R, K, Ca and Mg), and of micronutrients (Cn, Fe, Zn and Mn) in the leafs of five forest species: Araribá rosa (Centrolobium robustum), Guarantã (Esenbeckia leiocarpa), Ipê roxo (Tabebuia heptaphylla), Genipapo (Genipa americana) e Joazeiro (Zizyphus joazeiro). The statistical analysis and interpretation of the data allowed the following conclusions : a) Concentrations of macro and micronutrients varied among the species. b) Concentrations of macro and micronutrients varied according to position of the leaf on the branch and also to the species.